Rural Water in Tanzania : High Investments, Low Returns - World Bank (World Bank, Washington, DC, 2018)
The purpose of the document is to lay out the reasons for a lack of progress in Tanzania's rural water sector. Its key messages include: stressing the additional progress that is needed to make Sustainable Development Goal (SDG) targets for water, in particular taking into account accessibility of functioning rural water points; the need to address the causes of high water point failure; and the need to address institutional constraints that have limited the capacity of investment to reach its desired return. The econometric analysis of water point failure reveals the importance of the choice of pump type in comparison to the promoter and management in explaining water point failure. Meanwhile, the institutional analysis points to a limited user participation and weak accountability mechanisms; blurred institutional roles and intergovernmental arrangements; and limited capacity of local government and community-owned water supply organizations.